The role of endoplasmic reticulum aminopeptidase ERAP2 pathogenic mutation rs1363907 in amoxicillin clavulanate-induced liver injury: a special case report - Zhan, Yan; Liao, Jin-Mao; Ye, Ling; Zhang, Long; Zhang, Zheng; Yin, Ji-Ye (Frontiers in Pharmacology, 2025)
Idiosyncratic hepatotoxicity is a type of drug-induced liver injury (DILI) that is unpredictable and clinically severe, and amoxicillin clavulanate (AC) is the most implicated drug in DILI worldwide. The clinical manifestations of amoxicillin clavulanate-induced liver injury (AC-DILI) are fatigue and jaundice, which some allergic features may accompany, but autoimmune phenomena are uncommon. Here, we describe a special case report of a patient with AC-DILI accompanied by autoimmune phenomena for the first time. The patient was a middle-aged Chinese woman who developed liver damage after taking AC for a period of time, with a RUCAM score of 6. The patient tested positive for antinuclear antibodies and had elevated levels of IgG. Human leukocyte antigen (HLA)-targeted sequencing results showed that the patient did not carry known AC-DILI-related HLA polymorphisms, but Sanger sequencing suggested that the patient had the ERAP2 rs1363907 mutation, which may be a pathogenic factor of AC-DILI in the patient. The patient’s progress notes, disease diagnosis, and treatment are summarized, and the role of ERAP2 pathogenic mutation rs1363907 in AC-DILI is discussed.